URGENSI PENDIDIKAN KARAKTER SEBAGAI PENGEMBANGAN MENTAL PESERTA DIDIK DI MTS. AS’ADIYAH PUTRA II PUSAT SENGKANG - Nurul Mawaddah (IAIN PAREPARE, 2017)
This article aims to describe mental, character education form, and the urgency of character education of learners in MTs.As'adiyah Putra II Sengkang Center. Type of research used in this research is qualitative research with descriptive analysis and phenomenology approach. The paradigm of this study is qualitative by using analytical induction. The main instrument in this study is the researcher herself with several types of instruments are: interview guides, observation guides, field notes, and Crosscheck. In data processing, the researcher did the reduction, displaying and conclusion. The results showed that learners’ character in MTs.As'adiyah Putra II Center of Sengkang at the low level, it was indicated by the low level of self-awareness, has not got a sense of satisfaction and still need to foster peer relationships among teachers, parents and social environment. The form of character education which were done: First, integrating the values of character in learning activities. Second, extracurricular activities.Third, providing understanding and appreciation of the values of characters that are integrated into each subject being taught.Fourth, Familiarizing prayers in congregation in school and lecture training.Fifth, recitations and barasanji.Sixth, the participation of the school community in developing mental learners.Seventh, designing a conducive school atmosphere.Character education in MTs.As'adiyahPuta II Sengkang Center is very important to prepare learners able to face challenges of increasingly complex life dynamics.